Prevalence of chronic kidney disease among Chinese adults with diabetes: a nationwide population-based cross-sectional studyResearch in context - Weiping Jia; Rong Yu; Limin Wang; Dalong Zhu; Lixin Guo; Jianping Weng; Hong Li; Mei Zhang; Xiaoqi Ye; Zhiguang Zhou; Dajin Zou; Qiuhe Ji; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: To date, comprehensive data on the distribution of chronic kidney disease (CKD), the most prevalent comorbidity in diabetes, among Chinese adults with diabetes is lacking. Additionally, research gaps exist in understanding the association between CKD and cardiovascular health (CVH), an integrated indicator of lifestyle and metabolic control, within a nationwide sample of Chinese adults with diabetes. Methods: A nationally community-based cross-sectional survey was conducted in 2018–2020. 58,560 residents diagnosed with diabetes aged 18–74 years nationwide were invited to participate, and 52,000 participants with complete CKD data were included in this study. CKD was identified by the presence of albuminuria (urine albumin-to-creatinine ratio ≥30 mg/g) and/or decreased estimated glomerular filtration rate (eGFR, <60 mL/min/1.73 m2). The latter was calculated using the CKD-EPI equation incorporating serum cystatin C and creatinine. CVH was evaluated using the “life's essential 8” (LE8) score, which ranged from 0 to 100 and included 8 components: diet, sleep duration, physical activity, nicotine exposure, hemoglobin A1c, blood pressure, non–high-density lipoprotein cholesterol, and body mass index. The total LE8 scores were categorized into low (0–49), middle (50–79), and high (80–100) according to the American Heart Association. The associations of albuminuria and decreased eGFR with potential associated factors, including CVH, socioeconomic status, clinical characteristics, sub-regional divisions, comorbidities, treatments, and metabolic controls, were evaluated using survey logistic regression. Findings: The weighted prevalence rates (95% CI) of CKD, albuminuria, and decreased eGFR were 32.6% (31.3%–33.8%), 30.8% (29.6%–32.1%), and 5.5% (5.1%–5.9%), respectively. Among those with CKD, 25.7% had diabetic retinopathy (DR) and 22.3% had cardiovascular disease (CVD). The weighted prevalence rates of albuminuria and decreased eGFR were consistently higher among southern residents, rural residents, and individuals with more severe DR and a history of CVD than their counterparts (all p < 0.05). After adjustment for age, sex, sub-regional division, setting, educational level, annual household income, family history of diabetes, diabetes duration, glucose-lowering treatment, any DR, CVD, and drinking status, the logistic models showed that the odds ratios (ORs) (95% CI) for albuminuria and decreased eGFR were 0.46 (0.42–0.51) and 0.61 (0.55–0.67) for the participants with moderate scores, and 0.14 (0.10–0.21) and 0.28 (0.19–0.41) for those with high scores, compared with those with low total LE8 scores. Furthermore, the restricted cubic spline curves depicted that the disparities in the odds of having albuminuria or decreased eGFR among subpopulations grouped by sex, age, setting, and geographical region, significantly decreased and even disappeared in some cases as the LE8 scores increased. Interpretation: Chinese adults with diabetes are heavily burdened by CKD. Optimized CVH is central to reducing CKD risk across different subpopulations. Funding: National Key Clinical Specialty, the Chinese Academy of Engineering.